Environmental planning of the Buffelsfontein tertiary shaft - Dumka, Mychajlo (My University, 2015)
A comprehensive study was undertaken to minimize the Technical Environmental risks in extending the current BuffeUfontein Infrastructure, an additional 1 000 metres in depth, to a mean! rock breaking depth of 3 740 m below surface. A systematic approach was adopted in determining the environmental requirements, methods of ventilation and implications of physical limitations. Maximum re-use of existing ventilation Infrastructure and refrigeration machinery was pre-requisite. The determination of air reticulation capacities and chilling equipment operational limitations paramount.